Solving Economic Load Dispatch Problem UsingParticle Swarm Optimization Technique - Tiwari, Aditya; Godwal, Shanker; Nimje, Akhilesh (Turkish journal of computer and mathematics education, 2021)
Economic load dispatch (ELD)is one of the important problems ofpower system operation. Conventional methods like Lambda iteration methodare not efficientfor complex ELD problems. Particle swarm optimization is preferred in ELD problem due to its high performance.The Inertia Weight PSO and Constriction Factor PSO algorithms are performed on threeunit and sixunit systems. The analysis of ELD problem is performed by Conventional method and PSO method. In this paper,losses are neglected in the ELD problem. PSO algorithm obtains the best solution forELD problem.